Efecto del hacking ético en la infraestructura informática de la Notaría Cavides Luna - Punchana 2021 - Dávila Lage, Franco Aniello (2022)
The objective of this research was to determine the effect of ethical hacking on the computer infrastructure of the Cavides Luna - Punchana 2021 notary public office, consequently, of the thousands of cyberattack attempts that are being presented throughout Peru, in addition to complying with the that indicates the law 29733 "law of protection of personal data", posing the following question: What is the impact of ethical hacking to the computer infrastructure in relation to cybersecurity in the Cavides Luna - Punchana 2021 notary's office? For this, the general hypothesis was formulated "the application of ethical hacking improves the security of the computer infrastructure in terms of confidentiality, integrity and availability of information in the Cavides Luna - Punchana 2021 notary's office", the investigation was of an applied type, with non-experimental, analytical, longitudinal and prospective intervention. Collecting data through direct observation using observation files, which were processed with the IBM SPSS Statistics version 22 software, to determine the differences, the non-parametric Chi-square statistic of homogeneity was applied with a significance level of 5%; Obtaining as a result an improvement in terms of confidentiality and integrity from 0% to 48.1%, and in terms of availability from 0% to 51.9%, in terms of cybersecurity is concerned. Concluding that there is a significant difference in cybersecurity with respect to confidentiality, integrity and availability.